A Synthetic Overview of Benzoxazines and Benzoxazepines as Anticancer Agents. (16th January 2023) - Chatterjee, Indranil; Ali, Kasim; Panda, Gautam
Abstract: Benzoxazines and benzoxazepines are nitrogen and oxygen‐containing six and seven‐membered benzo‐fused heterocyclic scaffolds, respectively. Benzoxazepines and benzoxazines are well‐known pharmacophores in pharmaceutical chemistry, which are of significant interest and have been extensively studied because of their promising activity against various diseases including their wide range of anticancer activity. Several reports are known for synthesizing benzoxazine and benzoxazepine‐based compounds in the literature. Herein this review provides a critical analysis of synthetic strategies towards benzoxazines and benzoxazepines along with various ranges of anticancer activities based on these molecules that have been reported from 2010 onwards. This review also focuses on the structure‐activity relationship of the benzoxazine and benzoxazepine scaffolds containing bioactive compounds and describes how the structural modification affects their anticancer activity. Abstract : Nitrogen‐ and oxygen‐containing seven‐ and six‐membered benzo‐fused heterocyclic scaffolds, benzoxazepines and benzoxazines, are the most important framework of many drugs. They have been synthesized using several methods and applied in a wide range of cancer treatments over the past few decades. This review summarizes synthetic modifications of these molecules and describes how structural modifications affect their anticancer activity over the last twelve years.